(untitled) (Fiep Bulletin - online, 2014)
The dance can be considered the emotional human’s first manifestation, that before the language, before the music, the need to extravasate a feeling made the man to dance (Achcar,1998). She has to provide to the individual a range of movements, where one can always know more starting from the offered existences and besides the movement, it can come to provide the social integration, where Garaudy (1980) he/she says that, when it "Dances it is to live and to express, with the maximum of intensity, the man’s relationship with the nature, the society, the future and with their gods". We Can is believed that that incentive can end if turning a motivation form for practice of those classes or for maintenance of the same. And the motivation for his/her time can have a direct connection with the practicing individual’s of dance classes’ emotion. That generated us intriguing subjects: which would the true emotions is generated by practicing children of dance classes? Are those moments positive or negative? We aimed at, using this motivation scale with base in the proofs idealized by Stipek (1998 apud Gil 2003), in their studies of this theme, to investigate the motivation levels in the dance classes in the city of Cable Cold-RJ, with female children, with age among 12 to 16 years of the project "New citizen". Results: 87,5% if they sit down happy when they make dance/education classes; 57,5% if they sit down sad when he/she doesn’t have dance/education classes; 55% if they sit down unfounded making the exercises related ace classes where they notice that the teachings don’t agree as it was him/her last and 50% if they sit down sad when it is corrected by the teacher. In that way we concluded that the dance/education, is an instrument of identification of the motivation levels, being her practice a positive influence so that the same ones participated in the project and continue inserted.